2008
DOI: 10.1111/j.1745-7262.2008.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an extract ofGanoderma lucidumin men with lower urinary tract symptoms: a double-blind, placebo-controlled randomized and dose-ranging study

Abstract: The extract of G. lucidum was well tolerated and an improvement in IPSS was observed. The recommended dose of the extract of G. lucidum is 6 mg in men with LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1
28

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 18 publications
0
24
1
28
Order By: Relevance
“…In addition, IPSS-QOL scores significantly improved (p=0.04) in the 6-mg group compared to placebo. No significant differences were found in urine flow rates between all groups after treatment [25].…”
Section: Ganoderma Lucidumcontrasting
confidence: 45%
See 1 more Smart Citation
“…In addition, IPSS-QOL scores significantly improved (p=0.04) in the 6-mg group compared to placebo. No significant differences were found in urine flow rates between all groups after treatment [25].…”
Section: Ganoderma Lucidumcontrasting
confidence: 45%
“…It has been shown to have strong 5-alpha reductase activity [24,25]. In a doubleblind, placebo-controlled randomized trial by Noguchi, 50 men received either various doses of G. lucidum or placebo over the course of 8 weeks.…”
Section: Ganoderma Lucidummentioning
confidence: 99%
“…Twenty studies (64.5%) were rated as low-quality randomized controlled trials (RCTs) (Jadad score f2), and the remaining 11 (35.5%) were rated as moderate-to-high (Jadad score o3). Table 2 presents the characteristics of the 11 moderate to high quality studies [26][27][28][29][30][31][32][33][34][35][36] that were selected for detailed analysis. All 11 of the studies were reported as randomized trials; only one (Study 6) 33 did not describe the method of randomisation.…”
Section: Description Of the Paper Selection Processmentioning
confidence: 99%
“…Five trials fulfilled the criteria of a double-blind study design and provided an appropriate description of the double-blind method (Studies 3, 4, 5, 6 and 11). 27,[31][32][33]35 Only four studies described the dropouts and listed the reasons (Studies 4, 5, 6 and 9). 27,28,32,33 Assessment by the Cochrane's risks of bias assessment Figures 2 and 3 display the proportion and summary of the high, low and unclear risk of bias of 11 studies with Jadad scores o3.…”
Section: Description Of the Paper Selection Processmentioning
confidence: 99%
“…Human trials have also been carried out with G. lucidum (Noguchi et al, 2008;Wachtel-Galor et al, 2004;Zhou et al, 2005), Lyophyllum decastes (Ukawa et al, 2007) and Hericium erinaceum (Kawagishi & Zhuang, 2008;Mori et al, 2009); these studies did not report any toxicological effects from consumption of these mushrooms.…”
mentioning
confidence: 97%